Education and its effect on human capital formation, growth and countries’ economic development (2011)
The effect of education on human capital formation and economic development of the countries, has been analyzed through theoretical and empirical studies. Classical and neoclassical theories of authors such as Smith and Solow respectively, the human capital theory by Danison, Schultz and Becker, and the theory of Sen’s development among others, had analyzed the effect of education on growth and economic and social development of the countries, showing that education is one of the determinants in increased productivity, which is projected in the generation of new technologies, processes and products, but probabily, it´smost significant effect are the private and social benefits, which includes, in terms of income generation, labor market integration, poverty reduction, ownership of cultural property and generally in the individual and social development.Human capital formation takes greater force in a globalized world characterized by constant economic, financial, technological, social and cultural changes, among others.